The Artisan Practices Of Integrating Hybrid Art Knowledge - Anak Michael, Valerie; Abd. Rahman, Khairul Aidil Azlin (2016)

(untitled)
This purpose of this paper is about artist’s practices in hybrid art knowledge. This paper examines the elements of artist’s practices in producing art work and as a tool for the dissemination of knowledge practice. There are 30 attributes extracted from hybrid art practices graph plot and the graph plot was analysed by using principal component analysis ( PCA ). All these attributes are discussed in two components which are artisan practices in hybrid art and hybrid art knowledge. In this multidisciplinary approach, it aims to discuss artist’s practices from four perspectives that are a combination and support, creative and style, media and character and art form. This paper also will discuss about artist’s practice affected artistic diversity, art space with gallery and understanding of audience to the concept of hybrid art knowledge. From the outcome of this research discussed how Conceptual Framework of Hybrid Art Knowledge integrated between artist, art space and audience to reflect on the impact of the local art scene